2022
DOI: 10.1016/j.jenvman.2021.114082
|View full text |Cite
|
Sign up to set email alerts
|

Identifying barriers to sustainable apple production: A stakeholder perspective

Abstract: Apple is one of the most important cash crops in China. However, negative economic, environmental and social impacts are associated with its production. This study aims to apply a holistic systems perspective to understand existing problems associated with apple production in China and use this information to improve its sustainability. A structured survey was administered to farmers (n = 245) in Shandong and Shanxi provinces, combined with semi-structured interviews with apple supply chain stakeholders (n = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 86 publications
(94 reference statements)
0
6
0
1
Order By: Relevance
“…In recent years, literature review confirmed that plenty of research articles had been published by researchers on SSCM corresponding to the green technological innovations (Wangsa et al 2022 ). Some researchers included it but not restricted to establishing the green technological innovations indicators for SSCM (Hussain and Malik 2020 ), examined and explored sustainable supply chain barriers and drivers and practices (Govindan and Hasanagic 2018 ), classified and filed the barriers hierarchy index to SSCM in the Chinese and Pakistani manufacturing industry (Jin et al 2022 ; Waqas et al 2018 ) and enabler of sustainable supply chain operations in Pakistani manufacturing industry (Hussain et al 2021 ). The bibliometric analysis has provided directions to scholars, who are managing plenty of research publications in the field of SSCM considering technological innovation.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, literature review confirmed that plenty of research articles had been published by researchers on SSCM corresponding to the green technological innovations (Wangsa et al 2022 ). Some researchers included it but not restricted to establishing the green technological innovations indicators for SSCM (Hussain and Malik 2020 ), examined and explored sustainable supply chain barriers and drivers and practices (Govindan and Hasanagic 2018 ), classified and filed the barriers hierarchy index to SSCM in the Chinese and Pakistani manufacturing industry (Jin et al 2022 ; Waqas et al 2018 ) and enabler of sustainable supply chain operations in Pakistani manufacturing industry (Hussain et al 2021 ). The bibliometric analysis has provided directions to scholars, who are managing plenty of research publications in the field of SSCM considering technological innovation.…”
Section: Introductionmentioning
confidence: 99%
“…This study investigated eight major apple-producing areas in China from 2007 to 2020. The production and supply capacity of these major apple-producing areas are key to maintaining the security of China’s apple industry [ 15 , 24 ]. Regional differences among China’s provinces are related to their geographical environments.…”
Section: Methodsmentioning
confidence: 99%
“…In 2021, the planting area and scale of apple production in China accounted for more than 50% of the global total [ 14 , 15 ]. However, as a result of labor shifts, the overall quality of apple farmers in China, as well as the gender ratio, has changed dramatically.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Petani memiliki pengetahuan baru dan muncul keinginan untuk menanam apel kembali (Kuntari dan Madiyanto, 2019). Menurut Jin et al (2022), upaya pemberian fasilitas budidaya apel yang berkelanjutan memerlukan kebijakan yang mendorong petani dapat mengadopsi inovasi dan teknologi baru yang menghasilkan manfaat sosial dan lingkungan, serta membantu petani mengurangi risiko kerugian finansial dalam produksi. .…”
Section: Rekomendasi Kebijakanunclassified